Mushroom worker’s lung: A case of acute occupational hypersensitivity pneumonitis in a young female - Rebayudeen, S M Mohamed; Prakasam, Praveen Kumar; Sivaranjani, T (Indian Journal of Case Reports, 2025)
Hypersensitivity pneumonitis (HP) is an interstitial lung disease triggered by an exaggerated immune response to inhaled environmental antigens. Occupational exposure plays a major role in disease etiology. A 26-year-old female presented with a 7-day history of fever, productive cough, breathlessness, and weight loss. Clinical and radiologic findings were suggestive of HP. A detailed occupational history revealed exposure to organic antigens in a mushroom factory without protective measures. She showed marked clinical improvement with corticosteroid therapy. HP remains an underdiagnosed condition. Detailed occupational history and early recognition are a key to appropriate management and prevention of chronic sequelae.